2016
DOI: 10.1016/j.inoche.2015.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Anti- Mycobacterium tuberculosis activity of platinum(II)/ N , N -disubstituted- N ′-acyl thiourea complexes

Abstract: Synthesis, characterization and anti-Mycobacterium tuberculosis assays of new platinum(II)/dppf/N,Ndisubstituted-N′-acyl thiourea complexes with general formulae [Pt(dppf)(L)]PF 6 , [dppf = 1,1′-bis (diphenylphosphino)ferrocene; L = N,N-disubstituted-N′-acyl thioureas] is reported. The complexes were characterized by elemental analysis, molar conductivity, IR, NMR (1 H, 13 C and 31 P{ 1 H}) spectroscopy. The spectroscopic data are consistent with the complexes containing one dppf and one O, S chelated ligand. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Also in the region of d = À138-158 a multiple signal of the PF 6 À , functioning as outer-sphere anions for the complexes is observed, in accordance to the molar conductivity measurements for these complexes (see experimental section). These data are consistent with those obtained for some thiosemicarbazones and N,N-disubstituted-N 0 -acyl thioureas complexes [10,21,27]. 6 , and 8, [Pd(dppf)(N,N-diphenyl-N 0 -thiophenylthioureato-k 2 O,S)]PF 6 , are shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…Also in the region of d = À138-158 a multiple signal of the PF 6 À , functioning as outer-sphere anions for the complexes is observed, in accordance to the molar conductivity measurements for these complexes (see experimental section). These data are consistent with those obtained for some thiosemicarbazones and N,N-disubstituted-N 0 -acyl thioureas complexes [10,21,27]. 6 , and 8, [Pd(dppf)(N,N-diphenyl-N 0 -thiophenylthioureato-k 2 O,S)]PF 6 , are shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…Acylthiourea, a simple ligand derived from readily available and inexpensive starting materials, is well known for its versatile coordination via three donor atoms (O, N, and S). Complexes of platinum,, ruthenium, palladium, cobalt and copper, containing acylthiourea are known to have biological and catalytic potentials. In recent years there is a widespread demand for architecting heterogeneous catalysts because of their inherent advantages such as easy removal from the reaction medium, recyclability, cleaner process and no metal contamination with the product.…”
Section: Introductionmentioning
confidence: 99%
“…While thioamide and thiourea compounds possess S and N donor atoms, acylthiourea derivatives offer a donor set that consists of O, N and S atoms for coordination to metal centers (Figure ). Heteroleptic Ru II , Pt II , Pd II , and Co III[11e] complexes of acylthiourea ligands indicated that coordination occurred through the sulfur and oxygen atoms in a bidentate mode (Figure 1, ix ). The Ru II complexes were demonstrated to be more potent antiproliferative agents than the corresponding acylthiourea ligands and cisplatin with IC 50 values in the low micromolar range .…”
Section: Introductionmentioning
confidence: 99%
“…The Ru II complexes were demonstrated to be more potent antiproliferative agents than the corresponding acylthiourea ligands and cisplatin with IC 50 values in the low micromolar range . The Pt II complexes showed activity against M. tuberculosis , while the anticancer, antibacterial, and/or antileishmanial activity of Co III[11e] and Cu I[11a] complexes were reported. In the latter case, the acylthiourea ligands behaved as monodentate ligands by coordinating through its S atom to the Cu I center (Figure 1, viii ) .…”
Section: Introductionmentioning
confidence: 99%